Pancasila Dan Kebhinekaan: Studi Etnografi Kehidupan Beragama Dan Berbudaya di Kalangan Mahasiswa PPKn - Nepa Bureni, Estalin; Laoere, Matheos Eduard; Koli, Jefrianus; Ledang, Daniel Zakeos Beri (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze in depth how students of the Pancasila and Civic Education Study Program (PPKn) at Nusa Cendana University understand and practice Pancasila values in religious and cultural life in the multicultural campus environment of East Nusa Tenggara. Using a qualitative ethnographic approach, data were collected through participant observation, semi-structured interviews with ten students from diverse religious and ethnic backgrounds, and documentation of campus activities. Data analysis was conducted using domain analysis, taxonomic analysis, component analysis, and cultural theme analysis to reveal subjective dynamics. The results show that Civic Education students internalize Pancasila through daily interactions such as interfaith mutual assistance and participation in cultural activities, which strengthen tolerance and unity amid the challenges of identity polarization and intergroup friction. The main influencing factors include the contextual Civic Education curriculum and local traditions in NTT, although the dynamics of globalization still give rise to hate speech in the digital space. These findings affirm the function of Pancasila as an ethical foundation and practical guideline for diversity in higher education.